Postpartum depression on the neonatal intensive care unit: current perspectives - Tahirkheli NN; Cherry AS; Tackett AP; McCaffree MA; Gillaspy SR (Dove Medical Press, 2014)
Noor N Tahirkheli,1 Amanda S Cherry,1 Alayna P Tackett,2 Mary Anne McCaffree,3 Stephen R Gillaspy11Section of General and Community Pediatrics, Department of Pediatrics, University of Oklahoma Health Sciences Center, Oklahoma City, OK, USA; 2Department of Psychology, Oklahoma State University, Stillwater, OK, USA; 3Section of Neonatal-Perinatal Medicine, Department of Pediatrics, University of Oklahoma Health Sciences Center, Oklahoma City, OK, USAAbstract: As the most common complication of childbirth affecting 10%–15% of women, postpartum depression (PPD) goes vastly undetected and untreated, inflicting long-term consequences on both mother and child. Studies consistently show that mothers of infants in the neonatal intensive care unit (NICU) experience PPD at higher rates with more elevated symptomatology than mothers of healthy infants. Although there has been increased awareness regarding the overall prevalence of PPD and recognition of the need for health care providers to address this health issue, there has not been adequate attention to PPD in the context of the NICU. This review will focus on an overview of PPD and psychological morbidities, the prevalence of PPD in mothers of infants admitted to NICU, associated risk factors, potential PPD screening measures, promising intervention programs, the role of NICU health care providers in addressing PPD in the NICU, and suggested future research directions.Keywords: neonatal intensive care unit, postpartum depression, mothers